Speech Act Analysis in the Talk Show Hitam Putih on Trans 7 - Anabokay, Yanrini Martha; Langkameng, Oce Antipas; Kale, Maneie Bengu; Fanggidae, Yenssy Mervilen (Universitas Persatuan Guru 1945 NTT, 2022)
The study aims to find out the types of speech acts and the types of speech acts are mostly used in the talk show hitam putih on Trans 7. In this research, the writer used descriptive method. The media was used in this study is the youtube video of the talk show hitam putih on Trans 7. The presenter and the guess sta stars of talk show hitam putih became the subject of the research. Then, the utterances uttered by the presenter and the guess stars became the object of this study. The criteria that were used by the writer in order to analyze the data were based on the types of speech acts given by Austin in (Levinson, 1997:236). The result of this research shows that (1) there are three types of speech acts found in the talk show hitam putih on Trans 7, namely; Illocutionary speech act, lucutionary speech act and perlocutionary speech act; (2) In this study, the illocutionary act that mostly used in talk show Hitam Putih are asking clarity and statement.